2020
DOI: 10.3390/microorganisms8010088
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Ice Plant Growth-Promoting Endophytic Bacterium Halomonas sp. Strain MC1 to Identify the Genes Involved in Salt Tolerance

Abstract: Salt stress is an important adverse condition encountered during plant and microbe growth in terrestrial soil ecosystems. Currently, how ice plant (Mesembryanthemum crystallinum) growth-promoting endophytic bacteria (EB) cope with salt stress and regulate growth and the genes responsible for salt tolerance remain unknown. We applied RNA-Seq technology to determine the growth mechanism of the EB Halomonas sp. MC1 strain and the genes involved in salt tolerance. A total of 893 genes were significantly regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…A quantitative analysis confirmed that R. aquatilis JZ-GX1 can produce IAA and siderophores and has the ability to dissolve phosphorus under salt stress. Our results are consistent with those reported by Fatima et al (2020) . Alcaligenes AF7 has the ability to dissolve phosphorus under salt stress, and this ability promotes the ability of plants to grow under salt stress.…”
Section: Discussionsupporting
confidence: 94%
“…A quantitative analysis confirmed that R. aquatilis JZ-GX1 can produce IAA and siderophores and has the ability to dissolve phosphorus under salt stress. Our results are consistent with those reported by Fatima et al (2020) . Alcaligenes AF7 has the ability to dissolve phosphorus under salt stress, and this ability promotes the ability of plants to grow under salt stress.…”
Section: Discussionsupporting
confidence: 94%
“…Many Halomonas sp. exhibit salt tolerance and can improve plant growth under salt stress conditions [48,[55][56][57]. Bacillus is common genera among the endosphere niche of diverse plants, where they play an important role in plant protection and growth stimulation [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted with cDNA library preparation in accordance with the method described by Zhang et al (2020) . The transcriptome was sequenced using an Illumina NovaSeq 6000 (150bp ∗ 2, Shanghai BIOZERON Co., Ltd.).…”
Section: Methodsmentioning
confidence: 99%